PENGEMBANGAN BAHAN AJAR MATEMATIKA BERBASIS MULTIMODAL PADA MATERI BARISAN DAN DERET - Nurul Kurnia; Subhan Ajiz Awalludin (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2022)
The purpose of this study is to develop multimodal-based mathematics teaching materials on row and series materials using assistance media in the form of Power Point, iSpring Suite 10 and Website 2 apk builder. The method used in this study is the Waterfall model. A tool used to analyze compilers using Unified Modeling Language (UML). The result of this research is an android application from the development of mathematics teaching materials on multimodal-based lineups and series materials. Multimodal is a way of learning by combining several techniques, be it sound, visual and also writing. Testing this application uses a black box test, which is testing an application, which can be tested on anyone and the android media used in this test is the Samsung Galaxy A51. Based on the test results, all the buttons in the application work as intended. Then it can be concluded that the application of mathematics to the material of rows and series can be used to train students' mathematical reasoning skills, especially in row and series materials. For this application, it is hoped that it can be developed again in various ways, be it animation, design, features, practice questions, various and more varied quiz questions and more effective programming so that it becomes more interesting.